Dilute magnetic semiconductor of ZnCoSe thin films: Structural, optical, and magnetic characteristics. Issue 7 (7th January 2019) - Shaaban, Essam R.; Mahasen, Mohamed M.; Soraya, Mohmoud M.; Yousef, El Sayed; Mahmoud, Safwat A.; Ali, Gomaa A. M.; Elshaikh, Haroun A.
Abstract: A series of Zn1− x Co x Se ( x  = 0, 0.025, 0.050, 0.075, and 0.100) films using were evaporated (thickness of 1 μm) using electron beam gun. The effect of Co doping on the structural, optical, and magnetic properties has been investigated. X‐ray diffraction studies confirm formation of zinc blend structure for all Zn1− x Co x Se films. The crystallite size increases and the lattice strain decreases with the increase in Co content. The elemental constituents were characterized by energy dispersive X‐ray. Optical studies showed an increase in refractive index and a decrease in energy gap with the increase in the cobalt doping. The dispersion of the refractive index has been analyzed in terms of the Wemple‐DiDomenico single oscillator model. The oscillator parameters including the single oscillator energy ( E o ), the dispersion energy ( E d ), and the static refractive index ( n 0 ) were estimated. Magnetization measurements via vibrating sample magnetometer showed a hysteresis loop and confirmed room‐temperature ferromagnetism in Co‐doped ZnSe films.